2014
DOI: 10.1007/978-1-4939-1139-4_15
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Expression and In Vitro Refolding of Limited Fragments of the Notch Receptor and Its Ligands

Abstract: Prokaryotic expression of limited fragments of the Notch receptor and its ligands followed by in vitro refolding has been used for the production of the significant amounts of protein required for structure determination by X-ray crystallography or nuclear magnetic resonance spectroscopy. As an illustration of the protocol for the production of these EGF-containing constructs we have focused on a limited fragment of human Notch 1 that contains three calcium-binding EGF domains, hNotch-111-13. Following charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Protein expression, isotopic labeling, refolding, and purification protocols have been described previously ( Muranyi et al., 2004 , Weisshuhn et al., 2015a , Weisshuhn et al., 2015b , Whiteman et al., 2014 ). Protein fragments were expressed in Escherichia coli BL21 cells transformed with a pQE30 (Qiagen)-based protein expression construct and a pREP4 plasmid for control of expression via the Lac Repressor.…”
Section: Methodsmentioning
confidence: 99%
“…Protein expression, isotopic labeling, refolding, and purification protocols have been described previously ( Muranyi et al., 2004 , Weisshuhn et al., 2015a , Weisshuhn et al., 2015b , Whiteman et al., 2014 ). Protein fragments were expressed in Escherichia coli BL21 cells transformed with a pQE30 (Qiagen)-based protein expression construct and a pREP4 plasmid for control of expression via the Lac Repressor.…”
Section: Methodsmentioning
confidence: 99%
“…Protein expression, purification and refolding Protein expression and purification was carried out as described previously for similar constructs (Weisshuhn et al 2014;Knott et al 1996;Whiteman et al 2014). Constructs Schematic pictures of the EGF8-11, EGF9-11 and EGF11-13 constructs, discussed in this study, are shown.…”
Section: Methods and Experimentsmentioning
confidence: 99%
“…Protein expression, purification and refolding Protein expression and purification was carried out as described previously for similar constructs (Weisshuhn et al, 2014, Knott et al 1996, Whiteman, Redfield, and Handford 2014. Constructs were expressed in E. coli BL21 cells transformed with a pQE30 (Qiagen) based protein expression construct and a pREP4 plasmid for control of expression via the Lac Repressor.…”
Section: Methods and Experimentsmentioning
confidence: 99%